Accelerated aging in sorghum sacarino seeds Sorghum bicolor (L.) Moench - Deuner, Cristiane; Almeida, Andréia da Silva; Testa, Matheus Luiz; Suñé, Anna dos Santos; Tunes, Lilian Madruga de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
Saccharin sorghum is cultivated from seeds, requiring adequate production, harvesting and drying techniques to ensure the availability of quality seed and, therefore. The objective was to evaluate the initial quality by studying a more adequate methodology of the accelerated aging test for the evaluation of the physiological potential of sorghum seeds. The research was conducted in the Laboratory of Seed Analysis of the Department of Plant Science, Federal University of Pelotas, in Pelotas, Rio Grande do Sul. A completely randomized experimental design with 4 replicates was used. Four lots of sweet sorghum seeds were used. First we assessed the quality of the seeds by the following tests: water content, germination, first count and emergency field. Following evaluation of initial quality, lots were submitted to the traditional aging test and use saturated saline, in periods of 12, 24, 48, 72, 96 and 120 hours at 41 °C. Exposure of seeds for 24 hours at 41 °C in accelerated aging with saturated NaCl and use for 48h at 41 °C in traditional accelerated aging are suitable to differentiate batches of sweet sorghum seeds.